TDP1 and TOP1 as targets in anticancer treatment of NSCLC: Activity and protein level in normal and tumor tissue from 150 NSCLC patients correlated to clinical data. (February 2022) - Jakobsen, Ann-Katrine; Yuusufi, Sakineh; Madsen, Line Bille; Meldgaard, Peter; Knudsen, Birgitta R.; Stougaard, Magnus
Highlights: TDP1 activity and protein amount is upregulated in the tumor tissue in NSCLC. TOP1 activity and protein amount is upregulated in the tumor tissue in NSCLC. TDP1 and TOP1 activity and protein correlates in normal and tumor tissue in NSCLC. TOP1 and TDP1 upregulation and correlation is independent of clinical parameters. Dual targeting of TDP1 and TOP1 may be preferable over TOP1 drugs alone. Abstract: Objectives: Topoisomerase 1 (TOP1) is a drug target used in anticancer treatment of various cancer types. The effect of the TOP1 drugs can be counteracted by the enzymatic activity of tyrosyl-DNA phosphodiesterase 1 (TDP1). Thus, to elucidate the relevance of combining TDP1 and TOP1 as drug targets for anticancer treatment in NSCLC, TDP1 and TOP1 was for the first time quantified in a large cohort of paired normal and tumor tissue from NSCLC patients, and data were correlated between the two enzymes and to clinical data. Materials and methods: TDP1 and TOP1 activity and protein concentration were measured in paired normal and tumor tissue from 150 NSCLC patients using TDP1 and TOP1 specific biosensors and ELISA. TDP1 and TOP1 activity and protein concentration were correlated to clinical data. Results: TDP1 and TOP1 activity and protein concentration were significantly upregulated from normal to tumor tissue for the individual patients, but did not correlate to any of the clinical data. TDP1 and TOP1 activity were upregulated in 89.3% and 82.7% of the patients, respectively, and correlated in both normal and tumor tissue. The same tendency was observed for protein concentration with an upregulation of TDP1 and TOP1 in 73.0% and 84.4% of the patients, respectively. The activity and protein concentration correlated in normal and tumor tissue for both TDP1 and TOP1. Conclusion: The upregulations of TDP1 and TOP1 from normal to tumor tissue combined with the observation that TDP1 and TOP1 did not correlate to any of the clinical data indicate that both proteins are important for development or maintenance of the tumor cells in NSCLC. Correlations between TDP1 and TOP1 indicate a biological dependency and potential co-regulation of the enzymes. These observations is encouraging in relation to using TOP1 and TDP1 as targets in anticancer treatment of NSCLC.